Colonisation of the proximal intestinal remnant in newborn infants with enterostomy: a longitudinal study protocol. Issue 11 (24th November 2019) - Barreiros Mota, Inês; Marques, Cláudia; Faria, Ana; Neto, Maria Teresa; Cordeiro-Ferreira, Gonçalo; Virella, Daniel; Pita, Ana; Pereira-da-Silva, Luís; Calhau, Conceição
Abstract : Introduction: The gut microbiota plays a main role in the maintenance of host's health. Exposure to different conditions in early life contributes to distinct 'pioneer' bacterial communities in the intestine, which shape the newborn infant development. Newborn infants with congenital malformations of the gastrointestinal tract (CMGIT), necrotising enterocolitis (NEC) and spontaneous intestinal perforation (SIP) commonly require abdominal surgery and enterostomy. The knowledge about the colonisation of these newborns' intestine by microorganisms is scarce. This protocol is designed to explore the microbial colonisation over time of the proximal intestinal remnant in newborn infants who underwent surgery for CMGIT, NEC or SIP and require enterostomy. Methods and analysis: The literature about microbiota colonisation in newborn infants with enterostomy was reviewed and an observational, longitudinal, prospective study was designed. The infants will be recruited at the Neonatal Intensive Care Unit of the Hospital Dona Estefânia, Centro Hospitalar Universitário de Lisboa Central. Samples of the enterostomy effluent will be collected every 3 days, through 21 days after the first collection. The microorganisms colonising the proximal intestinal remnant will be identified using the 16S rRNA sequence analysis and a subset of microorganisms will be quantified using real-time PCR. This protocol may serve as basis for future observational and interventional studies on the modulation of the intestinal microbiota (eg, probiotics) on short and long-term outcomes in this population. Ethics and dissemination: This study protocol was approved by the Ethics Committee of Centro Hospitalar Universitário de Lisboa Central (441/2017) and by the Ethics Committee of NOVA Medical School, Universidade Nova de Lisboa (n°50/2018/CEFCM). The results will be spread through peer-reviewed publications and presentations at international scientific meetings. Trial registration number: NCT03340259 .